The low frequency structure-borne sound problem in multi-storey timber buildings and potential of acoustic metamaterials: A review. (October 2022) - Gibson, Bernard; Nguyen, Tuan; Sinaie, Sina; Heath, David; Ngo, Tuan
Abstract: In recent years, advances in timber engineering, combined with an associated evolution in building codes, have led to a significant expansion of multi-storey timber construction worldwide – helping to unlock timber's potential as a sustainable alternative construction material. This expansion has intensified a long-recognised need for more effective methods to attenuate low frequency (20–120 Hz) structure-borne sound. Being lighter and less stiff than steel and concrete, timber structures tend to offer less inertial and elastic resistance to impact forces and existing sound insulation treatments provide inadequate attenuation in the 20–120 Hz range. This leads to high levels of low frequency noise transmission and deleterious effects on occupant comfort. This review lays out the fundamentals of the problem, the significance of its effects on building occupants, and the shortcomings of existing technologies developed to solve it. In this context, potential new metamaterial-based approaches are then considered. In acoustic metamaterials, previously impossible properties, such as infinite or negative mass density, stiffness, or bulk modulus, have been achieved, opening new possibilities for wave attenuation. However, practical issues, relating to structural capacity, imposed additional mass, and the breadth of attenuated frequency ranges, remain challenges to be solved. This article provides a broad overview of the characteristics that make low-frequency structure borne sound attenuation in multi-storey timber buildings so critical for occupant comfort and so difficult to achieve. It analyses the limitations of existing technologies and identifies nonlinear metamaterials that use vibro-impact oscillators to induce energy flow from low to high frequencies as having the best potential for overcoming those limitations. Highlights: Low frequency noise transmission leads to high levels of occupant dissatisfaction. Existing attenuation methods are ineffective in the low frequency range. Acoustic metamaterials have potential to overcome existing limitations. Linear metamaterials are limited in the bandwidth they can attenuate. Some nonlinear metamaterials show outstanding potential for broadband attenuation.